Money and Family Matter: Political Recruitment in the Golongan Karya Party of Banten Province - Ismanto Ismanto; Sjafari Sjafari; Listyaningsih Listyaningsih (Iapa Proceedings Conference, 2019)
Meritocracy is still a fundamental problem in political recruitment in Indonesia, especially in political parties. Although reform has penetrated all state institutions and the entire life of the nation and state, political parties became one of the institutions that remained unmoved by the old tradition even with several adaptations to follow the demands of democratization. This research was conducted with a qualitative approach to study the process of political recruitment in the Banten Province Golongan Karya Party, ahead of the 2019 General Election. It was chosen because of its existence as the most experienced major party. The results of the study prove that the poor face of political recruitment of legislative candidates is more determined by financial strength and nepotism. Formal selection is done, but the process is not accountable enough as well as the results. As a result, it will be closely related to the election of members of the legislature who have not only doubted their capabilities but also their integrity as reflected in the low quantity and quality of policies produced and the proliferation of corruption cases involving many legislative members at the central and regional levels.